2019
DOI: 10.1152/ajpheart.00670.2018
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase-like 2 depletion is protective in age-associated vascular stiffening

Abstract: Vascular stiffening and its sequelae are major causes of morbidity and mortality in the elderly. The increasingly accepted concept of “smooth muscle cell (SMC) stiffness syndrome” along with matrix deposition has emerged in vascular biology to account for the mechanical phenotype of arterial aging, but the molecular targets remain elusive. In this study, using an unbiased proteomic analysis, we identified lysyl oxidase-like 2 (LOXL2) as a critical SMC mediator for age-associated vascular stiffening. We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 29 publications
5
65
0
Order By: Relevance
“…Mice anesthetized with 2% isoflurane were placed on a heating pad, and their paws were taped to electrocardiogram electrodes. PWV was measured non-invasively as previously described by high-frequency Doppler (Indus Instruments, Webster, TX) at two points along the aorta: one point in the upper thoracic cavity and one point in the lower abdominal cavity (Hartley et al, 1997;Steppan et al, 2019). PWV was calculated as the separation distance divided by the pulse transit time between the two points.…”
Section: Pwv and Heart Rate Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice anesthetized with 2% isoflurane were placed on a heating pad, and their paws were taped to electrocardiogram electrodes. PWV was measured non-invasively as previously described by high-frequency Doppler (Indus Instruments, Webster, TX) at two points along the aorta: one point in the upper thoracic cavity and one point in the lower abdominal cavity (Hartley et al, 1997;Steppan et al, 2019). PWV was calculated as the separation distance divided by the pulse transit time between the two points.…”
Section: Pwv and Heart Rate Measurementsmentioning
confidence: 99%
“…After slow acclimatization over 2 weeks, animals were restrained in a translucent plastic cone with the tail exposed. Blood pressure was determined by a tail cuff measurement system as described previously (Kent Scientific, Torrington, CT) (Wang et al, 2017;Steppan et al, 2019).…”
Section: Non-invasive Blood Pressure Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular stiffness assessed by pulse wave velocity (PWV) correlates independently with poor outcomes [6]. As reported in many previous studies, Steppan et al indicated that evaluation of vascular stiffness is an essential first step to develop targeted therapies [8]. These previous studies strongly indicated that we should select a mouse model in accordance with the properties of the mouse strain.…”
mentioning
confidence: 97%
“…Vascular stiffness is also highly predictive of major adverse cardiovascular events, such as perioperative myocardial infarction, heart failure, and death [6]. Furthermore, vascular stiffness is closely related to age-associated hypertension, which precedes the development of clinical hypertension [8]. To assess the pathophysiology of hypertension, researchers have conducted many experimental studies using mice [10][11][12][13][14][15], which will be increased.…”
mentioning
confidence: 99%